Bisnis Model Digital “Weverse” Pada Kelompok Musik Korea Bts - Pertiwi, Inten; Darmawan, Andreas James; Heptariza, Anita; Ramayu, I Made Satrya (Program Pascasarjana STIE Amkop Makassar, 2023)
The Korean music group BTS is the most historic group in the success of popularizing Korean culture in the packaging of boy bands. Behind this success, the BTS production and management house has adapted a lot of digital business models to meet the needs of their fans in the Weverse application. The purpose of this research is to make a study that explores the digital business model strategy carried out by BTS, in order to provide learning to develop a digital business model category for a local music group in the global market. The research method uses descriptive qualitative with an in-depth look at the Weverse application, both as social media, and as a marketplace specifically for their products; using literature data collection techniques, online media, and direct interaction with BTS fans in Indonesia. The results of this study are in the form of a Weverse digital business model framework, with various descriptions on application features, customer user access, and customer journeys. The research implications can be a guide for continuing ongoing research on similar topics, as well as having an impact on BTS fans in studying digital business models from a country's culture. Keywords: Digital Business Model, Weverse, BTS